Preliminary survey of the scale insects fauna in Kermanshah, western Iran - Torabi, M.; Vahedi, H.A.; Hodgson, C.J. (ENTOMOLOGIA HELLENICA, 2010)
The Coccoidea on cultivated and non-cultivated vegetation in Kermanshah, western Iran, were investigated between 2007 and 2009. More than 63 samples from cultivated and non-cultivated plants were collected. The identified species mainly belonged to the following families: Diaspididae (12 species), Coccidae (7), Pseudococcidae (4), Margarodidae (3), Eriococcidae (2) and Ortheziidae (1). The economically important species are discussed. This project is part of an MSc on Coccoidea studies which has still some time to run and so we expect that more species will be found in future.